2009
DOI: 10.1016/j.ejpain.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The association between neighbourhood socio‐economic status and the onset of chronic widespread pain: Results from the EPIFUND study

Abstract: BackgroundCross-sectional studies have reported an inverse relationship between socio-economic status and the prevalence of chronic widespread pain (CWP). However, the extent to which this relationship is explained by psychological factors is unknown. The aim of this study was to examine the hypothesis that socio-economic status predicts the onset of CWP but that this relationship would be explained by psychological factors.MethodsSubjects from three diverse socio-economic areas were recruited into a populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
51
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 24 publications
(34 reference statements)
10
51
1
Order By: Relevance
“…This claim neither refutes the importance of lifestyle factors nor does it exclude the participation of yet additional risk factors, such as the adverse effects of non-steroidal anti-inflammatory drugs and other medications commonly used in this clinical context. The socioeconomic context also continues to deserve attention as it has been associated with both the prevalence of CWP47 48 and with higher overall cardiovascular and cancer mortality 49. Similar observations apply to sleep deprivation 50…”
Section: Discussionmentioning
confidence: 88%
“…This claim neither refutes the importance of lifestyle factors nor does it exclude the participation of yet additional risk factors, such as the adverse effects of non-steroidal anti-inflammatory drugs and other medications commonly used in this clinical context. The socioeconomic context also continues to deserve attention as it has been associated with both the prevalence of CWP47 48 and with higher overall cardiovascular and cancer mortality 49. Similar observations apply to sleep deprivation 50…”
Section: Discussionmentioning
confidence: 88%
“…A total of 10% of patients developed CP over 1 year and 15% of patients developed CP over 3 years. Both found an effect of SES on the development of CP but, for Davies et al, this effect disappeared after controlling for psycho logical factors, such as anxiety and depression, illness beliefs, symptoms and threatening life events [17]. The study by Jordan et al identified an effect of neighborhood general health on the likelihood of developing pain, and suggested that part of this was attributable to shared poor services, such as healthcare [18].…”
Section: What Factors Mediate An Association Between Cp and Ses?mentioning
confidence: 99%
“…These studies are supplemented by two prospective studies that took both area-and individuallevel measurements of SES at baseline [17,18]. A total of 10% of patients developed CP over 1 year and 15% of patients developed CP over 3 years.…”
Section: What Factors Mediate An Association Between Cp and Ses?mentioning
confidence: 99%
“…Nevertheless, only 3 patients had to be excluded after enrollment because their pain was found to be due to a specifi c condition, and in the remaining patients, physicians did not mention any specifi c relevant disease 6 or more months after inclusion. Depression, somatization, and other psychological causes of pain are probably not affected by vitamin D 3 but are likely prevalent in patients with chronic musculoskeletal pain [47][48][49] as well as in vitamin D defi ciency.…”
Section: Limitationsmentioning
confidence: 99%